2015
DOI: 10.1513/annalsats.201409-422oc
|View full text |Cite
|
Sign up to set email alerts
|

Health Care Resource Use and Costs of Two-Year Survivors of Acute Lung Injury. An Observational Cohort Study

Abstract: In this multisite study of 138 two-year survivors of ALI, 80% had one or more inpatient admission, representing a median (IQR) estimated cost $35,259 ($10,565-$81,166) per patient and $6,598,766 for the entire cohort. Hospital readmissions represented 76% of total inpatient costs, and having Medicare or Medicaid before ALI was associated with increased costs. With the aging population and increasing comorbidity, these findings have important health policy implications for the care of critically ill patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 64 publications
0
37
0
Order By: Relevance
“…Comparison with other studies reporting health care resource use or costs is difficult because of organizational differences at ICU and wider health service level and international differences in costing health care (35). However, compared with resource data for the first year after discharge summarized in a systematic review and a more recent publication (35,36), our cohort experienced comparable hospital readmission rates (1.1 compared with 0.6-2.8/patient) and days in hospital Some studies with control populations report results in conflict with our findings. A Canadian study reported that ICU survivors had a lower readmission rate compared with hospital control subjects during 3 years of follow-up (ARR, 0.80; 95% CI, 0.77-0.82) (37).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparison with other studies reporting health care resource use or costs is difficult because of organizational differences at ICU and wider health service level and international differences in costing health care (35). However, compared with resource data for the first year after discharge summarized in a systematic review and a more recent publication (35,36), our cohort experienced comparable hospital readmission rates (1.1 compared with 0.6-2.8/patient) and days in hospital Some studies with control populations report results in conflict with our findings. A Canadian study reported that ICU survivors had a lower readmission rate compared with hospital control subjects during 3 years of follow-up (ARR, 0.80; 95% CI, 0.77-0.82) (37).…”
Section: Discussionmentioning
confidence: 99%
“…Although hospital resource use dominates postdischarge costs (35,36), extending resource measurement beyond this to social care and societal costs, such as loss of earnings or the financial burden on caregivers, would have allowed a more comprehensive assessment of resource use (42).…”
Section: Discussionmentioning
confidence: 99%
“…These differences likely reflect distinct stakeholders’ perspectives. After hospital discharge, ARF survivors experience high rates of hospital readmission and unemployment(2, 44) creating a direct financial burden for patients and caregivers. Similarly, clinical researchers were likely aware of mortality as a competing risk in evaluating functional outcomes (45, 46) and thus, universally viewed survival as essential whereas all caregivers on the panel had family members who were still alive years after ARF.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, hospital readmission before recovery of dysphagia symptoms (on the basis of patient self-report with medical records verification [30]) was evaluated as a binary variable.…”
Section: Measurement Of Patient- Icu- and Hospital-related Exposurementioning
confidence: 99%